Pengembangan Aplikasi Scratch untuk Mendorong Pembelajaran Matematika Kolaboratif di Kelas - Barra P Praja; Nur Hikmah; Sinta Wati; Sigit Raharjo (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
The purpose of this research is to encourage student collaboration through technology-based learning media by utilizing Scratch software in fraction material for grade VII students. The research method used is Multimedia Development Life Cyle (MDLC) development. The trial of learning media was conducted on Parents’ Hope students. The results showed that the Fraction Explorer media designed as a math learning media was effective to encourage student collaboration in the classroom that presents the concept of fraction operations using Scratch application. Participants' responses to the developed media gave positive results, with an average score of 77% for each questionnaire indicator given in the “very good” category. Thus, there is a need for research to determine the effectiveness in learning and developing learning media and games to encourage group cooperation on different topics.